2008
DOI: 10.1021/bp0497886
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Response and Apoptosis in Newborn Lungs after Meconium Aspiration

Abstract: An important feature of meconium-instilled newborn lungs is an inflammatory response and apoptotic cell death. It was recently demonstrated by our group and supported by several other investigators in a relatively short period of time. Apoptosis exists also in healthy lungs, but in meconium-instilled lungs its level is usually dramatically higher. Apoptosis is characterized by loss of cell function, decrease in cell size, and its morphology. Apoptosis plays an important role in normal cell life, but increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…30,31 However, in MAS, the relationships between induction of cytokines and chemokines and pathophysiology are poorly understood, although levels of a few cytokines in sera of MAS patients have been investigated. 4 The assessment of various cytokines and chemokines levels is, therefore, important to precisely understand the mechanisms of lung injuries in MAS. IL-4, IL-10, and IL-13 act as anti-inflammatory cytokines and prevent abnormal inflammatory reactions in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…30,31 However, in MAS, the relationships between induction of cytokines and chemokines and pathophysiology are poorly understood, although levels of a few cytokines in sera of MAS patients have been investigated. 4 The assessment of various cytokines and chemokines levels is, therefore, important to precisely understand the mechanisms of lung injuries in MAS. IL-4, IL-10, and IL-13 act as anti-inflammatory cytokines and prevent abnormal inflammatory reactions in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…4,10,38,40 For example, de Beaufort et al 10 showed that the addition of meconium induces the production of IL-8 from A549 epithelial cells, and Zagariya et al 24 demonstrated that mRNA for TNF-␣, IL-6, and IL-8 is expressed in A549 epithelial cells stimulated by meconium. These results suggest that meconium itself is inducible for severe inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Last, lung instillation of meconium has been shown in animal models to induce airway epithelial cell and pneumocyte apoptosis via a mechanism that involves the reninangiotensin pathway and angiotensin II production (23)(24)(25)(26). Angiotensin type 1 receptors appear to predominate in the adult rat lung and modulate the chronic hypoxia induced pulmonary hypertension (27).…”
Section: Discussionmentioning
confidence: 99%